问题 解答题
脱式计算,怎样简便就怎样算.
101×
99
102
(4
5
6
-3
3
4
)÷(
3
14
+
2
7
(0.92+
2
25
)÷(4-2
7
9
36×(
2
3
+
1
6
-
3
4
13
8
×
3
7
+
3
8
×
3
7
4
9
÷〔
5
6
-(
1
6
+
1
3
)〕
答案

(1)101×

99
102

=(102-1)×

99
102

=102×

99
102
-
99
102

=99-

99
102

=98

1
34

(2)(4

5
6
-3
3
4
)÷(
3
14
+
2
7

=1

1
12
÷
7
14

=

13
12
×2

=

13
6

(3)(0.92+

2
25
)÷(4-2
7
9

=(

23
25
+
2
25
)÷1
2
9

=

9
11

=

9
11

(4)36×(

2
3
+
1
6
-
3
4

=36×

2
3
+36×
1
6
-36×
3
4

=24+6-27

=3;

(5)

13
8
×
3
7
+
3
8
×
3
7

=

3
7
×(
13
8
+
3
8
)

=

3
7
×2

=

6
7

(6)

4
9
÷〔
5
6
-(
1
6
+
1
3
)〕

=

4
9
÷(
5
6
-
1
6
-
1
3
)

=

4
9
÷
1
3

=

4
9
×3

=

4
3

单项选择题
单项选择题